Complex Alumina-Ferrous Coagulant for Effective Wastewater Purification from Hydrogen Sulfide - Erzhan I. Kuldeyev; Aysha E. Tastanova; Igor V. Bondarenko; Saniya S. Temirova; Ruslan E. Nurlybayev; Bibigul S. Botantayeva; Fardila M. Zaihidee (Advances in Materials Science and Engineering)
The article provides an overview of studies on the causes of the formation of hydrogen sulfide in anaerobic conditions of urban sewage systems and methods for neutralizing toxic reagent sulfur-containing compounds. It is noted that the presence of sulfur compounds and organic components in sewage flow leads to the formation and release of hydrogen sulfide into the atmosphere of settlements. Three main categories of methods for purifying sewage wastewater from hydrogen sulfide are presented. In this work, a complex alumina-ferrous coagulant has been developed from Kazakh raw materials. Based on natural ferruginous diatomite and middlings of sintered alumina, a complex alumina-ferrous coagulant has been synthesized, which is effective in purifying wastewater from hydrogen sulfide, accelerating the processes of sedimentation and clarification of sewage slurries. Experimental results also show that with the supply of increased amounts of coagulant, oil and oil films disappear from the surface of the cylinder, an almost complete purification of effluents from hydrogen sulfide compounds occurs, and the color of the liquid part is greatly reduced. In addition, the advantage of the developed reagent is that it is presented in the form of fine powder and can be easily dosed and added to a canalization pump station to interact with diluted hydrogen sulfide and be transported to sewage fields. Compared to other proposed methods in previous works, the reagent is suitable to be used directly in sewage systems such as sewage waters treatment plants and collectors to prevent hydrogen sulfide emission into the air atmosphere of populated areas, as well as at city sewage water treatment stations after air tanks and before secondary clarifiers to obtain better purified water suitable for watering agricultural plants.